MODELING OF REFLECTED CRACKS IN ASPHALT CONCRETE PAVEMENT OF HIGHWAYS - Kamenchukov, Aleksey; Ukrainskiy, Ilya; Bushuev, Nikina; Kim, Nikolay (Journal of Applied Engineering Science, 2021)
The paper considers the issues of crack resistance of multilayer systems made of asphalt concrete, namely: the causes and features of the occurrence and development of "reflected" cracks are investigated. A study of the operational state of highways was carried out and the prerequisites for the formation of defects on the pavement were determined, including the regional features of the work of the road structure. The authors comprehensively studied the causes of internal and external defects and deformations of asphalt concrete pavements. The most popular technologies for sealing cracks and restoring the pavement are considered, the experience of repairing roads in the western part of Russia, Europe and the USA is also investigated. The results of determining the rate of formation and development of defects in the surface of the exploited roads are presented. In laboratory conditions, work was carried out to simulate cracks in two-layer samples of fine-grained asphalt concrete. Test specimens with a height and diameter of 10 cm were made by molding and compacted in layers, a crack was laid in the lower layer of the specimen. After gaining strength, the samples were tested for compression. Analysis of the results of physical modeling made it possible to put forward an assumption about the existence of a relationship between the presence (absence) of internal defects in the coating and the strength of the structure. To confirm the hypothesis, mathematical modeling of the operation of a two-layer system in the GenIDE32 software package was performed. Evaluation of the stress-strain state by the finite element method showed the presence of characteristic zones of system weakening around the defect area. In a two-layer system, there is an increase in internal stresses and strains around the crack, as well as a decrease in the overall strength (stability) of the system. In conclusion, the influence of internal defects of asphalt concrete coatings on the process of formation of "reflected" cracks were identified.